Penyakit Mulut dan Kuku (PMK) : Etiologi, Patogenesis, Pencegahan dan Pengendalian Pada Ternak Berkuku Genap atau Belah - Sukoco, Hendro; Wahyuni, Sri; Utami, Sri; Cahyani, Annisa Putri; Andanawari, Suci; Siswanto, Ferbian Milas (Universitas Bengkulu, 2023)
Foot and Mouth Disease (FMD) was first reported in 1987 in Malang, East Java, caused by imported dairy cattle from the Netherlands. After 36 years of FMD freedom, the disease was re-introduced on 5 May 2022 in East Java. The disease is caused by a virus of the genus Aphthovirus of the Picornaviridae family, which affects even-toed or split-hoofed livestock, both wild and domesticated. Transmission of FMD virus from sick animals to other susceptible animals can occur directly and indirectly. FMD virus can be transmitted rapidly, entering the animal's body directly through the mouth or nose and replicating in epithelial cells in the nasopharyngeal area, then entering the blood (viremia), then multiplying in lymphoglandular glands and epithelial cells in the mouth and footpads resulting in vesicle lesions and blisters. Animals or livestock infected with FMD will show clinical symptoms such as fever up to 41oC, the formation of vesicles or blisters on the mouth, gums, tongue, nipples, and skin around the hooves, hypersalivation, weight loss, and livestock production. Handling and controlling FMD in livestock or animals can be done by isolating and quarantining sick animals, vaccination programs, biosecurity measures in animal husbandry, monitoring livestock traffic, and conducting surveillance.